Exploring the multifaceted challenges of gastrointestinal metastases in lung adenocarcinoma: a case report highlighting diagnostic dilemmas and therapeutic innovations - Xu, Xinxin; Zhou, Qian; Chen, Peng; Du, Chengzhou; Huang, Yonghua; Gao, Xiaoxin; Xu, Shumei; Wu, Jinling; He, Tianxiao; Li, Hongtao (Frontiers in Oncology, 2024)
BackgroundLung cancer, the primary cause of cancer-related deaths, often metastasizes early, commonly affecting the liver, brain, bones, and adrenal glands. Although gastrointestinal (GI) metastasis is rare, it poses significant diagnostic and therapeutic challenges and is frequently linked to severe complications.Case descriptionWe present a case of a 61-year-old male with a history of lung cancer who presented with intestinal obstruction. The initial diagnosis of poorly differentiated adenocarcinoma was confirmed by computed tomography (CT) and bronchoscopic biopsy. The patient underwent chemotherapy, after which he developed intestinal obstruction. Further imaging and histopathological analysis indicated GI metastasis. Despite treatment with both chemotherapy and immunotherapy, the patient experienced recurrent obstruction, necessitating surgical intervention. Postoperatively, he had another episode of perforation, which was addressed with an emergency laparotomy, revealing metastatic adenocarcinoma at the site of perforation.ConclusionsThis case highlights the complexities in diagnosing and treating GI metastases from lung cancer. It underscores the necessity for multimodal treatment strategies and underscores the urgent need for research focused on early detection methods to improve patient outcomes.